The determinants of FDI distribution across manufacturing activities in an Asian industrialising country: a case of Japanese FDI in Thailand - Talerngsri, Pawin (2001)
This research identifies and investigates the 'industry-level determinants' of FDI in the context of Asian industrialising countries by using the data on Japanese foreign direct investment in Thailand. It differs from previous empirical studies for non-industrialised countries in three important aspects. Firstly, the previous studies (e. g. Lall and Mohammad, 1983) focus on the determinants of FDI in terms of monopolistic characteristics of industries in which foreign firms operate (e.g. technological intensities and scale economies). The present study, on the other hand, examines the influences of locational-specific characteristics of host industries such as factor endowments, trade costs, and policy factors. More distinctively, it examines the effects of vertical (input-output) linkages among Japanese firms. These effects have rarely been investigated in the context of Asian industrialising countries. Thirdly, it constructs the highly disaggregated data on FDI (4-digit ISIC level), using a broad range of information gathered from various published sources. Such data allow the present analysis to examine in detail the 'pattern' and 'determinants' of FDI distribution across segmented stages of manufacturing production rather than broadly defined industrial sectors.